2016
DOI: 10.1002/2016gl068424
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for slab material under Greenland and links to Cretaceous High Arctic magmatism

Abstract: Understanding the evolution of extinct ocean basins through time and space demands the integration of surface kinematics and mantle dynamics. We explore the existence, origin, and implications of a proposed oceanic slab burial ground under Greenland through a comparison of seismic tomography, slab sinking rates, regional plate reconstructions, and satellite‐derived gravity gradients. Our preferred interpretation stipulates that anomalous, fast seismic velocities at 1000–1600 km depth imaged in independent glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 56 publications
1
21
1
Order By: Relevance
“…Also, the low-Vp zone beneath western Svalbard seems to be interrupted at depths of 460-610 km. Between 1,050 and 1,500 km depths beneath southwestern Greenland, we do not observe any large velocity anomalies, although many existing global tomography models (e.g., Ritsema et al, 2011;Simmons et al, 2010) show a common high-V region that has been interpreted as a subducted slab (Shephard et al, 2016). Toyokuni et al (2020) also revealed a high-Vp anomaly in the same region.…”
Section: Results Of Different Tomographic Inversionscontrasting
confidence: 56%
“…Also, the low-Vp zone beneath western Svalbard seems to be interrupted at depths of 460-610 km. Between 1,050 and 1,500 km depths beneath southwestern Greenland, we do not observe any large velocity anomalies, although many existing global tomography models (e.g., Ritsema et al, 2011;Simmons et al, 2010) show a common high-V region that has been interpreted as a subducted slab (Shephard et al, 2016). Toyokuni et al (2020) also revealed a high-Vp anomaly in the same region.…”
Section: Results Of Different Tomographic Inversionscontrasting
confidence: 56%
“…Our results show a remarkable high‐ Vp anomaly at depths of 1,200–1,500 km beneath southwestern Greenland (Figure 5 and the F‐F′ section in Figure 6). This feature corresponds well to a possible slab remnant suggested by Shephard et al (2016) using the existing global tomography models (section 1). This study provides a more detailed view of this high‐ Vp anomaly by enhancing the tomographic resolution beneath Greenland.…”
Section: Discussionsupporting
confidence: 87%
“…The lower mantle structure beneath Greenland has not been studied well. Shephard et al (2016) reported a high‐ V zone at depths of 1,050–1,500 km beneath southwestern Greenland, which is found to be a common feature in many global tomography models (e.g., Ritsema et al, 2011; Simmons et al, 2010) and is interpreted as a subducted slab.…”
Section: Introductionmentioning
confidence: 99%
“…The recent use of seismically identified slabs to validate, test or refine regional relative plate motions includes slabs located under North America 9 , the Pacific 10 , the Indian Ocean region 11 – 13 , Australia 14 , Siberia 15 , and Greenland 16 , amongst others. However, these studies often focus on a subset of one, two, or a small selection of available tomography models, and are often restricted to a single class of tomography data (e.g.…”
Section: Introductionmentioning
confidence: 99%